2023
DOI: 10.1186/s12879-023-08288-8
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir-associated resistance mutations after first-line treatment failure in Brazil

Abstract: Background Since January 2017, the recommended first-line antiretroviral regimen in Brazil is the fixed-dose combination of tenofovir plus lamivudine with dolutegravir (TL + D). According to the literature, integrase resistance-associated mutations (INRAMs) are rarely found upon virologic failure to first-line dolutegravir plus two nucleoside reverse transcriptase inhibitors. We evaluated the HIV antiretroviral genotypic resistance profile of patients referred for genotyping in the public healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…One cross-sectional study from Brazil reported that among 113 previously ART-naïve PLWH with confirmed VF while receiving DTG plus tenofovir disoproxil fumarate (TDF)/3TC, seven (6.2%) individuals had major INSTI DRMs [ 42 ] ( Supplementary Table S1 ). However, the size of the population receiving DTG plus TDF/3TC and the total number with VF was not reported in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One cross-sectional study from Brazil reported that among 113 previously ART-naïve PLWH with confirmed VF while receiving DTG plus tenofovir disoproxil fumarate (TDF)/3TC, seven (6.2%) individuals had major INSTI DRMs [ 42 ] ( Supplementary Table S1 ). However, the size of the population receiving DTG plus TDF/3TC and the total number with VF was not reported in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-sectional studies in which GRT is performed in persons with confirmed VF on a DTG-containing regimen provide an alternate mechanism for assessing the risk of emergent DTG resistance. We described six such studies including one from Brazil of 113 PLWH with confirmed VF on a first-line regimen of DTG plus two NRTIs [ 42 ] and five from Sub-Saharan Africa. The studies from Sub-Saharan Africa included approximately 214 individuals, most of whom had prior ART experience before initiating DTG treatment [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the review of their titles and abstracts, 232 publications were submitted for full-text review. Following full-text review, 36 publications were found to have reports of INSTI-naïve PLWH who developed one or more INSTI-associated DRMs while receiving DTG [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and 21 publications contained in vitro susceptibility results performed using the PhenoSense assay [ 32 , 33 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , ...…”
Section: Resultsmentioning
confidence: 99%
“…As ART and PrEP expand, HIVDR emergence is likely, to jeopardize HIV/AIDS eradication efforts. Dolutegravir (DTG), though known for its high genetic resistance barrier, has shown resistance elsewhere, particularly among ART-experienced individuals ( 23 ). While a recent Zimbabwe study found no DTG resistance among ART-naïve individuals ( 24 ), surveillance and monitoring of HIVDR among DTG users is crucial due to its widespread use and potential future treatment limitations ( 25 , 26 ).…”
Section: The Need For Strengthening and Enhancing Hivdr Surveillancementioning
confidence: 99%